Identification of sustainable development statements social component objects - T.V. Baranovska; A.P. Dykyi; O.M. Baryshnikova (Проблеми теорії та методології бухгалтерського обліку, контролю і аналізу)
The article deals with the issue of sustainable development statements social component. The social aspects of business are examined. The algorithm of reporting on sustainable development on accounting data is built based on the analyzed researchers’ approaches to the role of social accounting in the development of an enterprise and value to improve accounting. The authors analyze the component parts of social component on sustainable development and identify the issues of ensuring reporting on sustainable development, which require solving in order to build reliable indicators of non-financial reports. The classification of social activity costs with their division into the accounting objects is carried out.